Exchange rate pass-through and monetary policy: How strong is the link? - Stephen Murchison (Bank of Canada, 2009)
Several authors have presented reduced-form evidence suggesting that the degree of exchange rate pass-through to the consumer price index has declined in Canada since the early 1980s and is currently close to zero. Taylor (2000) suggests that this phenomenon, which has been observed for several other countries, may be due to a change in the behaviour of inflation. Specifically, moving from a high to a low-inflation environment has reduced the expected persistence of cost changes and, by consequence, the degree of pass-through to prices. This paper extends his argument, suggesting that this change in persistence is due to a change in the parameters of the central bank's policy rule. Evidence is presented for Canada indicating that policy has responded more aggressively to inflation deviations over the low pass-through period relative to the high pass-through period. We test the quantitative importance of this change in policy for exchange rate pass-through by varying the parameters of a simple monetary policy rule embedded in an open economy, dynamic stochastic general equilibrium model. Results suggest that increases in the aggressiveness of policy consistent with that observed for Canada are sufficient to effectively eliminate measured pass-through. However, this conclusion depends critically on the inclusion of price-mark-up shocks in the model. When these are excluded, a more modest decline to pass-through is predicted.
Keywords: F31; F41; E52; 330; Exchange rates; Transmission of monetary policy; Geldpolitik; Exchange Rate Pass-Through; Lebenshaltungsindex; Kanada